EVALUATION OF ANTIRADICAL SCAVENGER ACTIVITY OF EXTRACT AND COMPOUNDS FROM ETLINGERA CALOPHRYS STEMS - I, Sahidin; Wahyuni, Wahyuni; Malaka, Muh Hajrul; A, Jabbar; Imran, Imran; Manggau, Marianti A (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: This study was aimed to isolate and identify the chemical compounds from the methanol extract of the stems of Etlingera calophrys as well as to evaluate their potential as free radical scavengers. Methods: The isolated compounds were obtained using vacuum liquid chromatography (VLC) and radial chromatography techniques. The structures of these compounds were determined on the basis of their measured spectroscopic evidence (infrared, one dimentional (1D), and 2D nuclear magnetic resonance) and by comparison with literature data. The free radical scavenging activity of the methanol extract of the stems and the isolated compounds were measured using qualitative and quantitative 2,2-diphenyl-1-picrylhydrazyl (DPPH) assays. Results: Yakuchinone A (1), p-hydroxybenzoic acid (2), and stigmasterol (3) were successfully isolated and identified from the stems of E. calophyrs. The methanol extract and compounds 1â€“3 showed free radical scavenging activity with half maximal inhibitory concentration (IC50) values of 38.36, 39.07, 46.60, and 153.4 Î¼g/mL, respectively, as compared to ascorbic acid with an IC50 value of 10.53 Î¼g/mL. Conclusions: Yakuchinone A (1) and p-hydroxybenzoic acid (2) are first reported from the genus Etlingera. The presence of these compounds may contribute to the free radical scavenging activity of the methanol extract of the stems of E. calophrys. This finding suggested that E. calophrys may serve as a source of natural antioxidant compounds and could be used in the development of antioxidant herbal preparation.